Two surveys separated by almost a decade reveal the inexorable decline in sleep time in teens: Results of the National survey of middle and high schools in adolescents on health and substances (EnCLASS 2018), and the evolution since 2010. - Damien Léger; Virginie Ehlinger; Stanislas Spilka; Olivier Le-Nézet; Brigitte Fauroux; Victor Pitron; Emmanuelle Godeau (PLoS ONE)
Purpose We investigated total sleep time (TST) and sleep paradigms during schooldays and leisure days in teenagers, and compared the findings to results from 8 years before. Methods The EnCLASS epidemiological survey is a representative sample of thousands of French middle and high schoolers. Specific sleep questions allowed us to assess TST, sleep debt, too short sleep, and screen use. Sleep debt as was defined as a difference between the total sleep time (TST) during schooldays (TSTS) non-schooldays (weekends or vacations; TSTN) of over 2 hours. Too short sleep was assesses when TSTS was <  7 hours. We detailed results of the 2018 bivariable analysis and adjusted by sex, age, class level, academic delay and socio-economic level, allowing us to compare the 2018 and 2010 results. Results TST decreases constantly from the beginning of middle school (MS) to the end of high school (HS). In 2018, 26.7% of middle and 43.7% of high schoolers were in "sleep debt". Additionally, 13.8% of middle and 29% of high schoolers reported too short sleep (less than 7 hours) on schooldays (vs. 7.8% in middle and 25.1% in high school in 2010). In 8 years, the TSTS of middle schoolers decreases by an average of 20 minutes of sleep per night on weekdays, dropping from 8 h 35 min to 8 h 14 min. Regarding screens at bedtime, an increase of 36.8 points was observed on schooldays in MS between 6th and 9th grade, with 13.9% more in HS, in 12th grade. This included 40.6% of middle and 60.6% of high schoolers using internet before sleep on schooldays. Conclusion Faced with this trend, teachers and parents need to take preventive action to avoid an inexorable decline in teenagers' sleep.